Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00425-020-03339-9
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium oxysporum infection activates the plastidial branch of the terpenoid biosynthesis pathway in flax, leading to increased ABA synthesis

Abstract: Main conclusion Upregulation of the terpenoid pathway and increased ABA content in flax upon Fusarium infection leads to activation of the early plant's response (PR genes, cell wall remodeling, and redox status).Abstract Plants have developed a number of defense strategies against the adverse effects of fungi such as Fusarium oxysporum. One such defense is the production of antioxidant secondary metabolites, which fall into two main groups: the phenylpropanoids and the terpenoids. While functions and biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 54 publications
(61 reference statements)
1
27
0
Order By: Relevance
“…An increase in endogenous levels of ABA was also observed when plants were infected with pathogens, for e.g., Phaseolus by Colletotrichum (Dunn et al, 1990), flax by Fusarium (Boba et al, 2020), and nced5 mutant of Arabidopsis by Alternaria (Fan et al, 2009). Similarly, the clonal variation of chestnut susceptibility or resistance to Fusarium was related to ABA levels under infection (Camisón et al, 2019).…”
Section: Increased Aba Levels Under Different Stress Conditionsmentioning
confidence: 90%
“…An increase in endogenous levels of ABA was also observed when plants were infected with pathogens, for e.g., Phaseolus by Colletotrichum (Dunn et al, 1990), flax by Fusarium (Boba et al, 2020), and nced5 mutant of Arabidopsis by Alternaria (Fan et al, 2009). Similarly, the clonal variation of chestnut susceptibility or resistance to Fusarium was related to ABA levels under infection (Camisón et al, 2019).…”
Section: Increased Aba Levels Under Different Stress Conditionsmentioning
confidence: 90%
“…infection was considerably higher in Nike than in Regina at both 24 hpi and 48 hpi (see in S9 Table and Table 1). Activation of TFs already present in the cell that leads to increased production of plant hormones, critical for the development of plant immune response, like salicylic acid, jasmonic acid and ethylene or abscisic acid [36,37]. Generally, plant responses to biotrophic pathogens, which require live tissue to complete their life cycle, are regulated by the SA signaling pathway, whereas necrotrophic pathogens that degrade plant material are regulated by the ET and/or JA signaling pathways.…”
Section: Plos Onementioning
confidence: 99%
“…Numbers of differentially expressed chitinase and β-1,3-glucanase genes were higher in Nike compared to Regina variety at 24 hpi, while they were similar at 48 hpi (see in S9 Table and Table 1). It was previously shown that β-1,3-glucanase as well as chitinase are essential for flax resistance to Fusarium [37] PLOS ONE and transgenic flax plants overexpressing the β-1,3-glucanase gene showed lower susceptibility to this pathogen [44].…”
Section: Plos Onementioning
confidence: 99%
“…These oxygencontaining derivatives include alcohol, aldehyde, ketone, and carboxylic acid. It is derived from a methylene-dicarboxylic acid, and the basic frame for the ve-carbon unit, carbon for a single ring, multiple rings, open-chain terpene, open-chain terpene formula (C5H8) general formula, including steroid, carotenoids, plant hormones, and quinones [36]. Terpenoids are widely found in nature and are the main components of some plant essences, resins, and pigments (such as rose oil, eucalyptus oil, turpentine) [37].…”
Section: Discussionmentioning
confidence: 99%